Woodcut, "Tlingit Inside House Post" by Helmi Juvonen, ca. 1930-1950 (1930)
Helmi Juvonen (1903-1985) was a Seattle artist and a member of the Northwest school. Her parents were Finnish immigrants whose family moved to Seattle in 1918 where she attended Queen Anne High School and Cornish College of hte Arts. Helmi is best known for her prints, paintings, and drawings, and she had an interest in native art as shown in this woodcut. 1 Woodcut; Materials: rice paper --ink; Dimensions: 17 in.H x 11.75 in.W